Successful BCMA CAR-T Therapy for Multiple Myeloma With Central Nervous System Involvement Manifesting as Cauda Equina Syndrome—A Wandering Road to Remission - Wang, Yiyun; Wang, Linqin; Zeng, Yifan; Hong, Ruimin; Zu, Cheng; Yin, Elaine Tan Su; Zhao, Houli; Wei, Guoqing; Yang, Li; Jin, Aiyun; Hu, Yongxian; Huang, He (Frontiers in Oncology, 2021)
Multiple myeloma (MM) with central nervous system (CNS) involvement is rare with only 1% occurrence. So far, there is no standard and effective treatment for CNS MM, and the predicted survival time is fewer than 6 months. Here, we reported a case of MM with CNS involvement presented with cauda equina syndrome (CES) who achieved complete remission after anti-BCMA chimeric antigen receptor T (CAR-T) cell therapy (Chictr.org.cn, ChiCTR1800017404). The expansion of BCMA CAR-T cells was observed in both peripheral blood (PB) and CSF. The CAR-T cells peaked at 2.4×106/L in CSF at day 8 and 4.1×109/L in PB at day 13. The peak value of IL-6 in CSF was obtained 3 days earlier, and it was almost 5 times higher than in the PB. Next, the morphological analysis displayed that the nucleated cells were eliminated from 300 nucleated cells/μL in CSF after CAR-T cell treatment one month and the patient achieved functional recovery with regressed lesion in PET-CT. The case demonstrated that BCMA CAR-T cells are effective and safe in multiple myeloma with central nervous system involvement patient.